The Role of Health Information Systems to Enhance Health Services in Remote and Underserved Areas: Challenges and Solutions - Irmawati S; Rosdianah Rosdianah; Devin Mahendika; Asri Ady Bakri; Ian Astarina Mas'ud (Sean Institute, 2023)
Health Information Systems have the potential to enhance the accessibility and quality of health services in remote areas. However, limited infrastructure, user skills, data security, and limited resources pose obstacles to the implementation of Health Information Systems in remote areas. This study seeks to analyze the role of Health Information Systems, challenges and solutions in the implementation of Health Information Systems in remote areas, and recommendations for system features that support health services through a review of the relevant literature. The results of the research on implementation challenges indicate the development of an IT infrastructure, user training, robust data security, and a sustainable funding source. Health Information Systems with centralized patient databases, disease reporting systems, inventory management, and inter-facility integration can enhance data access, decision-making, coordination, and resource management. In conclusion, Health Information Systems are a crucial instrument for enhancing health services in remote areas. Effective implementation requires collaboration among healthcare providers, the government, and other stakeholders in order to maximize the potential of Health Information Systems and surmount existing obstacles